Dari aretē ke agapē: Rekonstruksi etika kebajikan Kristiani sebagai basis pendidikan karakter - Jonathan Leobisa (KURIOS, 2026)
The crisis of character in contemporary society demands a response that transcends merely technical pedagogical intervention. This article argues that a reconstruction of Christian virtue ethics, moving from the philosophical roots of Aristotelian aretē to the theological apex of agapē, provides a robust and integral foundation for character education in Christian religious education. Through an analytical-synthetic approach that brings classical moral philosophy into dialogue with systematic moral theology, this article traces the transformation of the concept of virtue from Aristotelian eudaimonism to Thomistic synthesis and, ultimately, to christological love ethics. Integrating MacIntyre's narrative virtue, Aquinas's doctrine of caritas as forma virtutum, and the pedagogical implications of Smith, Hauerwas, Dykstra, and Groome, this article offers a character education framework grounded in participation in divine love and actualized through community, formative practices, and faith narrative. The contribution lies in offering an integrative paradigm that bridges the philosophical and theological heritages to support the praxis of contextual Christian religious education in Indonesia.   Abstrak Krisis karakter yang melanda masyarakat kontemporer menuntut respons yang melampaui sekadar intervensi pedagogis teknis. Artikel ini mengajukan argumentasi bahwa rekonstruksi etika kebajikan Kristiani, yang bergerak dari akar filosofis aretē Aristotelian menuju puncak teologis agapē, menyediakan fondasi yang kokoh dan integral bagi pendidikan karakter dalam Pendidikan Agama Kristen. Melalui pendekatan analitis-sin-tetis yang mempertemukan tradisi filsafat moral klasik dengan teologi moral sistematika, artikel ini menelusuri transformasi konsep kebajikan dari eudaimonisme Aristotelian melalui sintesis Thomistik menuju etika kasih kristologis. Dengan mengintegrasikan perspektif MacIntyre tentang kebaikan naratif, doktrin Aquinas tentang caritas sebagai forma virtutum, serta implikasi pedagogis Smith, Hauerwas, Dykstra, dan Groome, artikel ini menawarkan kerangka pendidikan karakter yang bersumber pada partisipasi dalam kasih ilahi dan diaktualisasikan melalui komunitas, praktik-praktik formatif, dan narasi iman. Kontribusi artikel ini terletak pada penawaran paradigma integratif yang menjembatani warisan filosofis dan teologis bagi praksis PAK kontekstual di Indonesia.